Labor market performance and the rise of populism - Sergei Guriev (IZA World of Labor, 2020)
The recent rise of populism in advanced economies reveals major voter discontent. To effectively respond to voters' grievances, researchers and policymakers need to understand their drivers. Recent empirical research shows that these drivers include both long-term trends (job polarization due to automation and globalization) and the rise in unemployment due to the recent global financial crisis. These factors have undermined public trust in the political establishment and have contributed to increased governmental representation for anti-establishment parties.
Keywords: D7; J6; 330; populism; job polarization; global financial crisis